Evolution of periglacial dells and valleys during the Holocene in the vicinity of Łódź: https://doi.org/10.26485/AGL/2017/106/2 - Twardy, Juliusz (Acta Geographica Lodziensia, 2018)
Referring to the results of the research on periglacial dells and valleys conducted in the vicinity of Łódź by Professor H. Klatkowa in the 50s and 60s of the last century, the paper presents the Holocene evolution of the aforementioned denudation forms. Three main stages of this evolution have been identified: 1) filling of periglacial dells and valleys with anthropogenic delluvium, 2) fragmentation of Vistulian forms through gullies, 3) relief transformation of gullies and periglacial dells and valleys by tillage erosion. The issue of factors influencing the Neoholocene changes in the relief of dry dells and valleys has been addressed, emphasizing the role of increasing human impact and climate fluctuations. In this paper the age of the individual stages of the transformations of the periglacial dells and valleys have been identified. Their evolution began at the end of the Subboreal period and lasted almost entire Subatlantic period until the present time, with a particular intensity in the Middle Ages. Lithological characteristics of Neoholocene deposits filling the periglacial dells and valleys is also presented.